Renal denervation: a new life of the technology - T. Y. Chichkova; S. E. Mamchur; M. P. Romanova; E. A. Khomenko (Фундаментальная и клиническая медицина)
Renal denervation (RDN) is a method of the sympathetic nervous system modulation which has been specifically developed for the treatment of resistant hypertension. Initial reports demonstrating high efficiency of RDN in such patients propelled the development of the technology, yet a specific randomised controlled trial Symplicity HTN-3 did not show its benefits. Data from the subsequent RCTs SPYRAL HTN-OFF MED and SPYRAL HTN-ON MED have shown that RDN reduces both office and daily blood pressure, does not depend on the patient adherence, and is efficient in patients with uncontrolled hypertension even in the absence of drug therapy. This review summarises the data on the efficacy and safety of the technology, its organoprotective effects, and also discusses the benefits of the RDN in different patient groups.